Diet and habitat use of two sympatric species of Philodryas (Colubridae), in south Brazil - Hartmann, P. A.; Marques, OAV (Brill Academic Publishers, 2005)
Feeding habits and habitat use of the colubrid snakes Philodryas olfersii and P patagoniensis in southern Brazil are presented here. Philodryas olfersii and P patagoniensis are sympatric in the study area and both dwell in open and forested areas. Specimens preserved in collections and observations of snakes in the field yielded the data. Both species are diet generalists, feeding on small vertebrates, mainly frogs. Philodryas patagoniensis has a broader diet, a less variable frequency of food items, and fed on heavier prey than R olfersii. Seasonal variation in diet occurs in both species. The semi-arboreal Philodryas olfersii is more slender and has a longer tail than the terrestrial R patagoniensis, characters that may reflect differences in microhabitat use. There are a strong relationship between habitat use and frequency of a given food type. Differences in the use of food resources between P. olfersii and P patagoniensis seem to reflect differences in foraging microhabitats used by each species.